ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) DI RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - Yusmaini, Yusmaini; Devis, Yesica; Saputra, Guruh; Hamid, Abdurrahman (Ensiklopedia of Journal, 2024)
The Work accident cases Province of Riau in 2019 amounted to 14,325 cases, it was knew that unequal knowledge of officers related to HOSH problem that occurs at Ibnu Sina Hospital Pekanbaru. The purpose of reseacch was to determine the application of Occupational Safety and Health (OSH) at Ibnu Sina Islamic Hospital Pekanbaru. The method of research was qualitative with Rapid Assessment Procedure design, interviews used purposive sampling technique as well as field observations and documentation of the activities of the HOSH committee. The results showed that HOSH program had not been optimally implemented due to the lack of socialization and training related to HOSH to all hospital staff. It can be concluded that it was necessary to propose a schedule of socialization/training related to HOSH in the form of training and education TORs, routine HOSH committee meetings, direct supervision by the hospital director, monitoring and evaluation in the form of monev reports, proposals for OSH experts to become full-time, budget proposals for implementing HOSH programs such as internal and external training, procurement of educational stickers and banners related to HOSH. Keywords: Health, Occupational Safety, RSI Ibnu Sina Pekanbaru